Pengaruh Media Bulletin Board Terhadap Kemampuan Sains Anak Terkait Kelestarian Alam Dan Lingkungan Hidup Di Taman Kanak-Kanak Qatrinnada Kota Padang - Salsabila Anisyari; Yaswinda, Yaswinda (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to determine the effect of bulletin board media on children's science abilities in Qatrinnada Kindergarten, Padang City. and data analysis techniques using the normality test. The research results show that this value is significant for the experimental class and the control class. and is stated to be normally distributed, then the variance of the N-gain data for the experimental class and control class is the same or homogeneous. The results of data analysis show that the average pre-test score for the experimental class is 21.3 and post-test is 26.0, while the average pre-test score for the control class is 22.1 and post-test 22.8 based on hypothesis testing. . shows a sig (2-tailed) value of 0.00 < 0.05 and the effect size test value d= 1,2 is included in the strong category. Thus, it can be concluded that there is a significant influence of bulletin board media on science skills related to preserving nature and the environment in early childhood at Qatrinnada Kindergarten Padang.